Clinical profile of tracheo-bronchial foreign body inhalation at tertiary care center - Samor, Vivek; Kumar, Vijay; Chand, Deep; Gupta, Gaurav; ., Mamta; Agrawal, Manish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Inhalation of foreign bodies can be life threatening and are common in paediatric age group with peak incidence in the age group of 1-3 years. The objectives were to study the clinical profile of foreign body (FB) inhalation and to study the complications of tracheo-bronchial foreign body and rigid bronchoscopy. Methods: A cross-sectional hospital based diagnostic study conducted for 1 year, done on 50 patients with FB inhalation, included consecutively in study after obtaining informed consent. Patients were assessed and interviewed for socio demographic details and examined using chest X-ray PA view, routine investigations and pre-anaesthetic evaluation. After all investigations a diagnostic bronchoscopy under general anaesthesia was performed to extract the foreign body. Data were analyzed through tables and diagrams and appropriate test of significance by Epi Info software. Results: Total 50 FB inhalation cases (up to 10 years) in which 40% presented within 5 days to 2 weeks after inhalation. 92% were presents with cough and on chest examination 88% found to had decreased air entry, 72% presents with decreased movement and dull percussion on affected side. 70% of patients had abnormal chest X-ray finding. Foreign body found were groundnut (44%) followed by supari (32%) mostly in right main bronchus. We observed 10% patients with pneumonia, 4% had granuloma and 2% had bronchospasm. Conclusions: Prevention is best, but early recognition remains a critical factor in the treatment of FB inhalation in children.